An experimental study to establish a salt gradient solar pond (SGSP). (February 2019) - Faqeha, Hosam; Bawahab, Mohammed; Vet, Quoi Line; Faghih, Ahmadreza; Date, Abhijit; Akbarzadah, Aliakbar
Abstract: This paper describes the experimental method to establish a salinity gradient in a MgCl 2 solar pond (SGSP) at Bundoora East campus of Royal Melbourne Information of Technology (RMIT) University, Melbourne, Australia. The pond was instructed in 2001, with a 15 m 2 surface area. This experiment involves using saturated brine to establish the lower thermal storage (or convective) zone (LCZ) as well as the middle insulating layer in which the salinity decreases with height. This non-convective zone (NCZ) is proctored from mixings caused by the wind and the destabilizing effects of diurnal variation of the ambient temperature by an upper convicting layer (UCZ). In this top layer (UCZ) both the temperature and salinity are uniform. These properties increase with depth in the (NCZ). Density and temperature usually assume their maximum values at the interface between the NCZ and the lower convective zone (LCZ). Both these properties y are usually constant in the (LCZ).In order to set up the salinity gradient using an injection filling technic introduced by Zangrando technique (1980). In this method, the pond is first filled to half the depth of the planned gradient zone with highly concentrated salt water. Next, fresh water, or salt water of a low concentration, is injected horizontally into the brine through a diffuser. The novelty for this paper is investigation redistribution method experimentally using simple technic to find the required volume of injected fresh water.